2007
DOI: 10.1007/s00484-006-0081-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of temperature variation on suicide in five U.S. counties, 1991–2001

Abstract: Effects of weather variables on suicide are well-documented, but there is still little consistency among the results of most studies. Nevertheless, most studies show a peak in suicides during the spring season, and this is often attributed to increased temperatures. The purpose of this study is to test the relationship between monthly temperature and monthly suicide, independent of months or seasons, for five counties located across the United States. Harmonic analysis shows that four of the five counties disp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
1
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(55 citation statements)
references
References 44 publications
0
52
1
2
Order By: Relevance
“…So far, however, no specific meteorological condition can be labelled as "suicide weather" (Dixon and Shulman 1983;Yan 2000;Deisenhammer 2003;Lee et al 2006). Higher temperatures appear to increase the risk of suicide (Lee et al 2006;Page et al 2007;Preti et al 2007), but negative correlations have also been found (Souêtre et al 1987(Souêtre et al , 1989, as well as no correlation at all (Partonen et al 2004b;Dixon et al 2007). In Finland, drops in temperature on successive days during spring have been found to be related to suicide rates in northern Finland (Partonen et al 2004c).…”
Section: Introductionmentioning
confidence: 91%
“…So far, however, no specific meteorological condition can be labelled as "suicide weather" (Dixon and Shulman 1983;Yan 2000;Deisenhammer 2003;Lee et al 2006). Higher temperatures appear to increase the risk of suicide (Lee et al 2006;Page et al 2007;Preti et al 2007), but negative correlations have also been found (Souêtre et al 1987(Souêtre et al , 1989, as well as no correlation at all (Partonen et al 2004b;Dixon et al 2007). In Finland, drops in temperature on successive days during spring have been found to be related to suicide rates in northern Finland (Partonen et al 2004c).…”
Section: Introductionmentioning
confidence: 91%
“…Therefore, it appears that the seasonality of suicides is due to factors other than temperature. 9 Preti 7 reported that the number of suicide cases is positively correlated to the geographical latitude. This can be explained by the fact that regions located in northern part, are less exposed to the sun and consequently the mean temperature is lower than in southern regions.…”
Section: Resultsmentioning
confidence: 99%
“…Climatic and seasonal triggering factors, changes in local weather conditions can modify human behaviour and influence the suicidal rate. [5][6][7][8] Recent study 9 results that simple linear regression shows no correlation between suicide and temperature, therefore, it appears that the seasonality of suicides is due to factors other than temperature. However, other epidemiological studies [10][11][12][13] found higher suicidal rate in warmer seasons, mainly summer periods.…”
Section: Introductionmentioning
confidence: 94%
“…Numerous scientific publications have reported on the weather's influence on the incidence of different mental disorders, indicating different meteorological factors in accordance with the geographical location of a given area (e.g., Deisenhammer 2003;Dixon et al 2007;Fletcher 1988;Lee et al 2006;Linkowski et al 1992;McConville et al 2002;Persinger 1980Persinger , 1987Preti 1998;Ruuhela et al 2009;Salib et al 2007;Stoupel et al 1995, and references therein).…”
Section: Discussionmentioning
confidence: 98%